2017
DOI: 10.7897/2277-4343.083148
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices Towards Herbs and Herbal Products Among Health Sciences Students of a University in Uae

Abstract: Herbal products and supplements are a branch of CAM, and are consumed for several health purposes, and mostly without a medical advice. To assess the knowledge, attitudes, and practices toward these herbals, we conducted a college-based survey, distributed to 334 students of dentistry and pharmacy in a university in United Arab Emirates. The survey included questions about the herbals used, purpose of consuming them, drug-herbals interaction, and safety of herbal consumed. Among the sample, only 5% of students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…28 Similarly, according to Shavan et al, most of the health science students participating in the survey supported the fact that herbal products could be useful for the treatment of certain medical conditions and for promoting health. 29 In this study it was found that family was an important source of information on the use of medicinal herbs and herbal products. Other learning resources for medicinal herbs and herbal products were determined as the internet and friends.…”
Section: Discussionmentioning
confidence: 98%
“…28 Similarly, according to Shavan et al, most of the health science students participating in the survey supported the fact that herbal products could be useful for the treatment of certain medical conditions and for promoting health. 29 In this study it was found that family was an important source of information on the use of medicinal herbs and herbal products. Other learning resources for medicinal herbs and herbal products were determined as the internet and friends.…”
Section: Discussionmentioning
confidence: 98%